Comfort parameters and particulate matter (PM10 and PM2.5) in school classrooms and outdoor air - Alves, Célia (2013)
In January 2012, one kindergarten and eight elementary school classrooms were monitored. The campaign included simultaneous measurements, indoors and outdoors, of comfort parameters, CO, CO2 and particles. Automatic monitors using a light scattering technique were employed to measure PM10 continuously. During occupied periods, low volume samplers were used to daily collect PM2.5 samples, which were subsequently analysed for carbonates, organic carbon (OC), elemental carbon (EC) and water soluble inorganic ions. With regard to comfort, the schools did not meet the recommended levels in many rooms. Indoor-outdoor CO2 ratios between 3 and 12, and indoor levels much higher than 1000 ppm during the occupied periods, indicate the highly inadequate ventilation in these locations. The results clearly demonstrate that there is a high level of exposure to particulate matter in these schools. The continuous measurements of PM10 suggest that the physical activity of pupils, which is assumed to be more marked in younger children, contributes to a constant process of resuspension of sedimented particles. In addition, peak PM10 concentrations coincident with cleaning activities suggest the need to change certain practices to improve cleanliness. Around 40% of the PM2.5 mass is composed of carbonaceous matter, with 4-5 times higher OC mass fractions than EC. It was observed that both OC and EC were significantly influenced by indoor sources. Water-soluble inorganic ions represented around 10-20% of the PM2.5 mass measured in classrooms. Excluding calcium, in general the ionic species were present at indoor-outdoor ratios of less than 1, suggesting the major origin in the outdoor air.